Discovery of Benzothiazole Amides as Potent Antimycobacterial Agents - Graham, James (Bioorg Med Chem Lett, 2018)
From a high throughput screening of commercially available libraries against nontuberculous mycobacteria and Mycobacterium tuberculosis, numerous hits were identified with moderate activity. Extensive medicinal chemistry optimization has led to a series of potent benzothiazole amide antimycobacterial agents. Replacement of the adamantyl group with cyclohexyl derivatives and further development of this series resulted in an advanced lead compound, CRS400393, which demonstrated excellent potency and a mycobacteria-specific spectrum of activity. MIC values ranged from 0.03-0.12 μg/mL against Mycobacterium abscessus and other rapid-grower NTM, and 1-2 μg/mL against Mycobacterium avium complex. The preliminary mechanism of action studies suggested these agents may target MmpL3, a mycobacterial mycolic acid transporter. The series has demonstrated in vivo efficacy in a proof of concept mouse model of M. abscessus infection.